Infrastructure Development and Income Distribution in Nepal - Bhattarai, Keshav Prasad (Economic Journal of Nepal, 2011)
This paper is an attempt to investigate the current pattern of infrastructural development and income distribution in Nepal. The pattern has been presented at the regional level on the period basis. Wide range of disparity is found within the regional level in the distributional pattern of infrastructural development and income. The nature of the distribution pattern of infrastructure in the regional level is identical with income distribution. The disparity existing in income distribution has direct relation with the pattern of the distribution of infrastructure.Key words: Infrastructure DevelopmentEconomic Journal of Nepal A Quarterly Publication of the Central Department of Economics, Tribhuvan University, Kirtipur, KathmanduVol. 30, No.3, July-September, 2007Page :175-183Uploaded date: 21 July, 2011